2013
DOI: 10.1016/j.hrthm.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of image-based simulation to estimate ablation target in human ventricular arrhythmia

Abstract: Background Previous studies suggest that MRI with late gadolinium enhancement (LGE) may identify slowly conducting tissues in scar-related ventricular tachycardia (VT). Objective We tested the feasibility of image-based simulation based on LGE to estimate ablation targets in VT. Methods We conducted a retrospective study in 13 patients who had pre-ablation MRI for scar-related VT ablation. We used image-based simulation to induce VT and estimate target regions according to the simulated VT circuit. The est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 25 publications
3
140
0
Order By: Relevance
“…11 That retrospective study demonstrated that VARP results are superior to other current non-invasive clinical metrics, such as LVEF, grey zone volume, 26 scar volume, 27 or left ventricular mass, 28 as well as to the invasive EP testing. These results point to the translational potential of VARP in being used as an effective patient selection tool for prophylactic ICD implantation.…”
Section: Discussionmentioning
confidence: 97%
“…11 That retrospective study demonstrated that VARP results are superior to other current non-invasive clinical metrics, such as LVEF, grey zone volume, 26 scar volume, 27 or left ventricular mass, 28 as well as to the invasive EP testing. These results point to the translational potential of VARP in being used as an effective patient selection tool for prophylactic ICD implantation.…”
Section: Discussionmentioning
confidence: 97%
“…Electrophysiology of normal and diseased human cardiac tissue was represented using an extensively validated approach (35). Briefly, cell-and tissue-scale properties were assigned to all 3 regions in the ventricular mesh: normal myocardium, PIZ, and infarct.…”
Section: Methodsmentioning
confidence: 99%
“…We used a computational model of the diseased human ventricles reconstructed from clinical late gadolinium-enhanced MRI (LGE-MRI) scans of a patient with post-myocardial infarction VT (33). The modeling approach has been previously validated in infarct-related VT inducibility studies (12,34,35). Our laboratory pipeline for cardiac model reconstruction has been described in detail in previous work (12,(34)(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been performed to investigate the effects of fibroblasts on wave dynamics in cardiac tissue [6,7]; however, most of the studies, which consider fibroblast-myocyte (FM) coupling, deal with a homogeneous distribution of fibroblasts in the domain. But, the density of fibroblasts in a diseased cardiac tissue may not necessarily be homogeneous [8]. Therefore, it is important to study the effects of FM coupling on wave dynamics in a domain with heterogeneous distributions of fibroblast density.…”
mentioning
confidence: 99%